Emotional dysregulation in borderline personality disorder and its influence on communication behavior and feelings in romantic relationships - Miano, Annemarie (Behaviour research and therapy, 2017)
Dysfunction in romantic relationships constitutes one of the most burdensome symptoms of borderline personality disorder (BPD). The aim of this study was to ascertain how emotional dysregulation affects behavior and relationship related feelings of women with BPD in threatening conversations with their own romantic partner. Thirty couples in which the women were diagnosed with BPD and 34 healthy control (HC) couples were videotaped while discussing personally threatening (i.e., personal failure) and relationship-threatening (i.e., separation) themes. Third party raters evaluated stress and communication behaviors during the conversations. Relationship related feelings, i.e., closeness and relationship insecurity, were assessed by self-report. Overall, women with BPD were rated as more stressed in threatening situations than HC women and their partners, but not more stressed in relationship-threatening than personally threatening situations. A heightened stress response of women with BPD predicted more negative and less positive communication behaviors and a stronger decline in self-rated closeness to the partner compared to HC. Stress-induced increases in relationship insecurity were specific to women with BPD. Our results highlight the central role of emotional dysregulation in interpersonal dysfunctions of persons with BPD and the need to address individual emotion regulation strategies more explicitly in dyadic contexts.
Gesehen am 25.10.2017